Massive thymic hyperplasia in an adult: A rare case report and literature review. (2018) - Zou, Dawei; Luo, Honghe; Feng, Yanfen; Zeng, Bo; Lei, Yiyan
Highlights: A large mediastinal mass. Left thoracotomy. Chylothorax. First case of MTH in an adult. Abstract: Introduction: Massive thymic hyperplasia is an extremely rare disorder, with fewer than 60 cases reported so far. Majority of the previous cases occurred in neonates, infants, and older children. Presentation of case: A man was found to have an anterior mediastinal mass without any symptoms at 30 years of age. Operation was done successfully. The mass measured 112 mm × 191 mm × 184 mm and weighed 2141 g. Histological and immunohistochemical findings further confirmed the diagnosis of massive thymic hyperplasia. The complication of postoperative chylothorax occurred, which has not been previously reported in MTH. After undergoing conservative treatment, the patient finally recovered. Discussion: This is the first case of massive thymic hyperplasia reported in an adult (defined as ≥ 18 years old). Chylothorax is one of the potentially fatal complications. However, we carried out effective treatments, which are educational and clinically interesting to surgeons and clinicians. Conclusion: Although not previously reported, massive thymic hyperplasia could also be found in adults. The main treatment for massive thymic hyperplasia is surgical removal. Good clinical effects on post-thymectomy chylothorax are available after undergoing conservative treatment.